Incidence and Management of Vascular Injuries after Invasive Cardiac Catheterization in Children - Aqil, Arifa; Abqar, Shaad; Mirza Kamran, Mohammad; Azam Haseen, Mohammad; Moaaz Kidwai, Mohammad (Indian Journal of Nursing Sciences, 2024)
Background: Vascular injuries after cardiac catheterization are well documented in adult population. The incidence of vascular injuries after pediatric cardiac catheterization is not as well defined. With the advent of therapeutic cardiac catheterization in pediatric patients, the incidence of vascular complications is likely to increase. Purpose: The aim of the study was to determine the incidence and management of vascular injuries associated with pediatric cardiac catheterization as an initial experience of in a newly established pediatric center. Methods: This retrospective and observational study was conducted on 268 children with congenital heart disease who have undergone cardiac catheterization either as diagnostic procedure or a therapeutic intervention between March 2018 and August 2019. Patient records were reviewed to obtain demographic, procedural, and treatment data. Patients were analyzed for the incidence and the type of vascular injury seen and treatment given for the same. The type of vascular injury was divided in to major and minor based on severity of the injury. Results: Diagnostic cardiac catheterization was performed in 77 patients and interventions in 191 patients. A total of 62 (23.1%) patients developed some vascular injury out of which 60 (22.3%) cases had minor complication and 2 (0.7%) had major a complication. The most common type of vascular complication seen in our study was transient loss of femoral pulse. Conclusions: Vascular injury is common in children undergoing cardiac catheterization, majority of which are minor complications and can be managed conservatively. They are seen more commonly during therapeutic cardiac catheterization. Further studies with larger sample size are needed to identify the risk factors for vascular injury